Evaluation and updating of the ethnofloristic medicinal knowledge of the eastern zone of Aguascalientes, Mexico - Mendieta-Vázquez, Araceli Guadalupe; Martínez-Calderón, Víctor Manuel; Torres-González, Jorge Alejandro; Álvarez-Reyes, José; López-Santos, Armando; Meraz-Jiménez, Antonio de Jesús (Ecosistemas y Recursos Agropecuarios, 2024)
Mexico has great traditional knowledge of the use of medicinal plants, threatened by globalization and the standardization of educational systems. In Aguascalientes, the semiarid areas of the east are little studied on the ethnobotanical topic. The objective was to evaluate and update ethnobotanical knowledge of eastern Aguascalientes. Interviews, field trips, and collections of the mentioned medicinal plants were carried out. The Knowledge Wealth Index (KWI) and analysis of variance (ANOVA) were calculated by the age and sex of the interviewees. 52 medicinal species were identified, with main uses in the treatment of digestive, respiratory, renal, and traumatic diseases. Low KWI was obtained with a mean of 0.13 (limited knowledge), and without significant differences in knowledge between men and women, and age. The importance of documenting and preserving traditional knowledge and the use of medicinal plants in eastern Aguascalientes is highlighted.